University Supervisors' Expectations for Cooperating Teachers during a TVET Practical Traineeship in the Field of Physical Education - Melki, Hasan; Mrayeh, Meher (Journal of Technical Education and Training, 2020)
Expectations based on reflective research create a mentoring environment in which instructors and university directors can reflect on pre-service issues, thereby increasing the understanding of mentors and reducing student stress, particularly in physical education universities that offer technical and vocational education and training (TVET). Therefore, this study aimed to describe the expectations of university supervisors of cooperating teachers, as the main actors in the practical teaching traineeship in the field of physical education teaching. In this essence, data collection was carried out with 148 university supervisors that took an integral part in the studies. The information of the survey technique revolved around the following issue: "What are your expectations during a practical training period of the cooperating teachers? Â». It has been achieved that cooperating teachers were concentrated on being seen as colleagues that share experiences with their trainees and understand the merits of the profession, leaders who act as professional in supervision methods and creative in finding solutions, guides in choosing the appropriate strategies and in filling the gaps of the lessons, good listeners and tolerant in offending behaviors whether toward them or other trainees.